Interplay between charge-density-waves, disorder, and superconductivity in transition metal dichalcogenides - Aya Ali; Fatima Alshaali; Mejd Almheiri; Mahmoud Abdel-Hafiez (Results in Physics, 2025)
Transition metal dichalcogenides (TMDs) are a fascinating class of materials known for their various electronic properties and potential applications in nanoelectronics, quantum computing, and energy storage. This review explores the intricate interplay between charge-density waves (CDWs), disorder, and superconductivity in TMDs, highlighting the significant advances made in understanding these phenomena over the past decades. We discuss how doping and external pressure modulate the electronic structure and phase transitions in TMDs, providing insight into the mechanisms driving these changes. The dual role of CDWs and disorder in promoting or suppressing superconductivity is examined, with a focus on the conditions under which superconductivity emerges or is enhanced. This review also covers the latest experimental techniques and theoretical models used to study these materials, emphasizing the synergy between experimental observations and theoretical predictions. The review will present detailed Pressure–Temperature (P–T) Phase Diagrams of TMDs, with a specific focus on three key families: MSe2, MS2, and MTe2, where M represents the transition metal. Each subsection examines how external pressure influences the phase transitions and electronic structures of these materials, providing insights into the pressure-induced modulation of CDWs and superconductivity. Following this, the Doping-Induced Enhancement of Superconductivity in TMDs section investigates how chemical doping can alter the superconducting properties of TMDs. Subsections dedicated to MSe2, MS2, and MTe2 delve into the various doping strategies employed, the resulting changes in electronic behavior, and the implications for enhancing superconductivity. By examining past and recent findings, this paper aims to provide a comprehensive understanding of the dynamic relationships between CDWs, disorder, and superconductivity in TMDs, paving the way for future research and technological advancements in this rapidly evolving field.